Models for automatic generation of educational tasks: a comparative analysis - Butenko, Dmitry (Computer Tools in Education, 2026)
The article presents a comparative analysis of models for the automatic generation of assessment tasks for university courses in the context of a growing mismatch between student and instructor numbers and an increase in cases of academic dishonesty. The aim of the study is to compare existing generation models according to three criteria — task variability, effort required for implementation, and explainability of results — in order to reduce instructors’ workload while preserving the quality of the educational process. The methodology includes an analysis of publications from 2020–2025 and a classification of models into template-based, grammar-based, statistical, graph-based, recurrent neural networks, evolutionary algorithms, and large language models (LLMs). Key findings: LLMs outperform alternative approaches in the diversity of generated content and computational efficiency when pre-trained models are used. Template-based and grammar-based systems are constrained by low variability, evolutionary algorithms require significantly more time, and recurrent networks are inferior in maintaining semantic coherence. Critical drawbacks of LLMs are limited explainability and a tendency to hallucinate, which necessitates mandatory expert oversight of outputs. The work has practical relevance for developers of educational systems and for instructors seeking to scale instruction while retaining pedagogical control.